Identification, description and structural analysis of beta phospholipase A 2 inhibitors (sbβPLIs) from Latin American pit vipers indicate a binding site region for basic snake venom phospholipases A 2 - Fortes-Dias, Consuelo Latorre (2019)
Several snake species possess, in their circulating blood, endogenous PLA 2 inhibitors (sbPLIs) with the primary function of natural protection against toxic enzymes from homologous and heterologous venoms. Among the three structural classes of sbPLIs – named α, β, and γ − the β class (sbβPLIs) is the least known with only four identified sequences, so far. The last class of inhibitors encompass molecules with leucine rich repeats (LRRs) motifs containing repeating amino acid segments. In the present study, we identified and characterized putative sbβPLIs from the liver and venom glands of six Latin American pit vipers belonging to Bothrops and Crotalus genera. The inhibitor from Crotalus durissus terrificus snakes (CdtsbβPLI) was chosen as a reference for the construction of the first in silico structural model for this class of inhibitors, using molecular modeling and molecular dynamics simulations. Detailed analyses of the electrostatic surface of the CdtsbβPLI model and protein-protein docking with crotoxin B from homologous venoms predict the interacting surface between these proteins.